CAGE14-5 Cruise Report: Fram Strait – NW Svalbard - Mienert, Jürgen; Panieri, Giuliana; Gründger, Friederike; Hong, Wei-L.; Johnson, Joel; Plaza-Faverola, Andreia; Jansson, Per; Portnov, Alexey; Waghorn, Kate A. (CAGE – Centre for Arctic Gas Hydrate, Environment and Climate Report Series, 2023)
CAGE 14-5 cruise allowed to study the gas release from gas hydrated sub-seabed environments at the continental margin off NW and N-Svalbard and the transport and distribution of methane within the water column. We carried out acoustic profiling (18, 38 and 120 kHz) in the water column, CTD water sampling for gas analyses, seismic profiling (mini GI guns), bathymetry mapping (EM300), and sediment gravity coring (3m corer). Though water above gas flares may be enriched in methane, methanotrophic microbescan reduce the methane concentrations and thus the amount of methane that may escape from the seabed to the ocean, one of the topics investigated during this cruise The cruise may be known as: CAGE14_5_JM